1997
DOI: 10.1038/sj.bmt.1700803
|View full text |Cite
|
Sign up to set email alerts
|

Clonogenic capacity andex vivo expansion potential of umbilical cord blood progenitor cells are not impaired by cryopreservation

Abstract: SummaryFetal blood collected immediately after delivery has been was the aim of this study to evaluate whether cryopreshown to contain hematopoietic progenitor cells at similar servation procedures might heavily impair the clonoor higher frequency than those in bone marrow (BM).1 genic capacity, the feasibility of CD34 ؉ selection and the Therefore, umbilical cord blood (UCB), which is normally ex vivo expansion potential of UCB progenitor cells.discarded, has been evaluated as a source of UCB samples were col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
1
1

Year Published

1997
1997
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 3 publications
2
13
1
1
Order By: Relevance
“…The effects of cryopreservation have been investigated using other types of stem cells [1,22]. These results and our results indicate that the freeze-and-thaw process and long-term storage in liquid nitrogen do not critically alter the phenotype of rat AT-MSCs.…”
Section: Post-thaw Phenotyping Of At-mscs Fresh and Cryopreservedsupporting
confidence: 53%
“…The effects of cryopreservation have been investigated using other types of stem cells [1,22]. These results and our results indicate that the freeze-and-thaw process and long-term storage in liquid nitrogen do not critically alter the phenotype of rat AT-MSCs.…”
Section: Post-thaw Phenotyping Of At-mscs Fresh and Cryopreservedsupporting
confidence: 53%
“…25 Also, CD34 + selection is expensive, timeconsuming and associated with extensive manipulation. The mononuclear cell fraction of human umbilical cord blood may therefore represent the better starting cell population.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] Studies are under way to determine the feasibility of UCB banking for use in unrelated transplants. [3][4][5][6] However, the major concern for future transplant application in adult patients has been related to the low number of progenitor cells that could be obtained by a single UCB collection. Several studies suggested that UCB contains a higher proportion of hematopoietic progenitor cells as compared to adult BM [7][8][9] and therefore the lower number of nucleated cells, present in a single collection, might be compensated by a higher proportion of primitive cells.…”
Section: Introductionmentioning
confidence: 99%